Immobilized Pt Complex Compounds as Catalysts for the Oxidation Reactions of Small Molecules - Ludmila P. Oleksenko; Vitaly K. Yatsimirsky; Ludmila A. Belyakova; Ol'ga Yu; Ol'ga Boldyreva (Adsorption Science & Technology)
A heterogeneous catalyst for the oxidation of small molecules has been prepared by the immobilization of Pt II and Pt IV complex compounds on the surface of amorphous macroporous silica. The structure of the surface platinum complex compounds has been established by means of vibrational and electronic spectroscopy while the catalytic activity of the catalyst was investigated for the hydrogen (or carbon monoxide) oxidation reaction by molecular oxygen under mild conditions.